2015
DOI: 10.1016/j.cub.2015.08.031
|View full text |Cite
|
Sign up to set email alerts
|

The Pro-apoptotic STK38 Kinase Is a New Beclin1 Partner Positively Regulating Autophagy

Abstract: SummaryAutophagy plays key roles in development, oncogenesis, cardiovascular, metabolic, and neurodegenerative diseases. Hence, understanding how autophagy is regulated can reveal opportunities to modify autophagy in a disease-relevant manner. Ideally, one would want to functionally define autophagy regulators whose enzymatic activity can potentially be modulated. Here, we describe the STK38 protein kinase (also termed NDR1) as a conserved regulator of autophagy. Using STK38 as bait in yeast-two-hybrid screens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
68
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(76 citation statements)
references
References 44 publications
(82 reference statements)
7
68
1
Order By: Relevance
“…Depletion of Beclin1, a key regulator of autophagy [42], also caused increased anoikis (Supplementary Figure S7) and interfered with anchorage-independent growth of HK-HRasG12V (Supplementary Figure S4). Considering that Beclin1 can function upstream of STK38 upon autophagy induction [29], these observations further strengthen the notion that STK38-mediated detachment-induced autophagy is critical to support oncogenic Ras signalling in order to antagonise anoikis and subsequently to promote anchorage-independent growth. In full agreement with this concept, we also detected considerably elevated STK38 kinase activity upon detachment of HK-HRasG12V cells (Figure 4M, 4N), as assessed by Thr444 phosphorylation of STK38, an established readout for STK38 kinase activity [27].…”
Section: Resultssupporting
confidence: 60%
See 4 more Smart Citations
“…Depletion of Beclin1, a key regulator of autophagy [42], also caused increased anoikis (Supplementary Figure S7) and interfered with anchorage-independent growth of HK-HRasG12V (Supplementary Figure S4). Considering that Beclin1 can function upstream of STK38 upon autophagy induction [29], these observations further strengthen the notion that STK38-mediated detachment-induced autophagy is critical to support oncogenic Ras signalling in order to antagonise anoikis and subsequently to promote anchorage-independent growth. In full agreement with this concept, we also detected considerably elevated STK38 kinase activity upon detachment of HK-HRasG12V cells (Figure 4M, 4N), as assessed by Thr444 phosphorylation of STK38, an established readout for STK38 kinase activity [27].…”
Section: Resultssupporting
confidence: 60%
“…However, to our surprise, we found that STK38 supports the survival of Ras-transformed human cells upon cell detachment. Given this observation and that our research recently revealed that STK38 positively promotes autophagy in adherent cells [29], we therefore postulated that STK38-mediated autophagy might support anoikis resistance and/or anchorage-independent growth in Ras-transformed cells. Indeed, STK38 knockdown resulted in diminished detachment-induced autophagy and anchorage-independent growth, paralleled by increased anoikis.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations